Role of Gender in Influencing Consumers’ Attitude Towards Online Advertising - Verma, Meghna; R., Saranya (Indian Journal of Marketing, 2014)
Internet revolution has led to the emergence of an e-generation era, where every aspect of life is taken online. So is the case with business, where the Internet has widened the horizon of promotion through advertising. Online advertising is a universe in itself, with different ways to present the promotional message of a company, each with a different level of effectiveness and impact on consumers. This necessitates the marketers to understand the attitude of consumers towards online advertisements in order to better target the advertisements to the right consumers in the right way. The paper attempted to fill the research gap in the area of online advertisements and thus explored the attitude of consumers towards online advertisements, the preference of content, attraction, and formats of online advertisements and the impact of online advertisements on consumers’ purchase decisions. The results of the study revealed that there was no significant influence of gender on respondents’ attitude towards online advertisements, and that respondents’ preference of online advertisements reflects their price sensitivity and preference to animation.